Scientific Opinion of Flavouring Group Evaluation 410 (FGE.410): 4', 5, 7‐trihydroxyflavanone from chemical group 25 (phenol derivatives containing ring‐alkyl, ring‐alkoxy, and side‐chains with an oxygenated functional group). (15th November 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) of EFSA was requested to deliver a scientific opinion on the implications for human health of the flavouring substance 4′, 5, 7‐trihydroxyflavanone or naringenin [FL‐no: 16.132], in the Flavouring Group Evaluation 410 (FGE.410), according to Regulation (EC) No 1331/2008 of the European Parliament and of the Council. The substance occurs naturally in grapefruits, oranges and tomatoes. It is intended to be used as a flavouring substance with flavour‐modifying properties in specific categories of food. Information on specifications and manufacturing of [FL‐no: 16.132] were considered adequate; however, data on stability in food are incomplete. The Panel noted that the available genotoxicity studies have significant shortcomings and are insufficient to conclude on the genotoxic potential of naringenin. Therefore, [FL‐no: 16.132] cannot be evaluated through the Procedure. Additionally, the Panel noted that inhibition of CYP 450 by [FL‐no: 16.132] has been clearly demonstrated in animal species in vivo which implies that the substance may interact with the metabolism and elimination of medicines and no convincing information is available that this does not pose a risk to humans at the estimated levels of exposure. To continue with the safety assessment of [FL‐no: 16.132], a bacterial gene mutation assay and an in vitro micronucleus assay (according to OECD guidelines 471, 487 and GLP) are required. Even if these studies do not indicate a genotoxic potential, additional toxicological data are needed to finalise the evaluation.